Academia and Society: Reading Michel Houellebecq’s Submission as an Academic Novel - Nurit Buchweitz (Studies in 20th & 21st Century Literature, 2025)
The article explores the relations between academia and society and the role of academicians in public and social life as represented in Michel Houellebecq’s 2015 novel Submission. Faithful to the author’s postmodernist poetics of destabilization and deconstruction, the novel problematizes the question of the responsibility and commitment of academia to society. The first part advances a reading of Submission as an academic novel narrative and elucidates its adherence to the genre by tracing features, topoi, and devices endemic to the genre. The second part goes on to interpret key scenes that demonstrate the satirical handling of academia, chiefly the juxtaposition between the faculty life in which the protagonist is embroiled on campus and the political intrigue taking place outside the gates of academia. The two divergent directions in which Houellebecq leads us are the over-involvement in politics, on the one hand, serving political interests with dire implications on research and teaching, and, on the other hand, the under-involvement in political life, which amounts to the ivory tower disengaging from the teeming reality below it.
Keywords: Michel Houellebecq; Submission; academic novel; satire; academia